2006
DOI: 10.1385/bter:114:1:115
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Serum Magnesium Measurement as a Biomarker of Acute Falciparum Malaria Infection in Adult Patients

Abstract: Serum magnesium concentration was measured in 80 adult patients (age range: 18-40 yr) presenting with acute, uncomplicated falciparum malaria infection and a control group of 20 age-matched, healthy individuals. The mean serum magnesium concentration in the patients was 1950.0 +/- 10.0 microg/dL. The control serum magnesium was 640.0 +/- 40.0 microg/dL. This represents an over threefold increase in serum magnesium levels above normal value, p < 0.01. The key pathogenic event in acute falciparum malaria infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…The present study revealed a significant (p<0.01) decrease in the magnesium level of the P. falciparum infected blood samples as compared to the P. falciparum free sample. This is however contrary to the result obtained in a study by Garba who observed an increase in the plasma magnesium level of malaria patients suffering from P. falciparum parasite [34]. This disparity might be due to the different parasite counts and stages presented by the patients used for the study.…”
Section: Levels Of Electrolytes (Ca Mg K Na) In P Falciparum Infecontrasting
confidence: 99%
“…The present study revealed a significant (p<0.01) decrease in the magnesium level of the P. falciparum infected blood samples as compared to the P. falciparum free sample. This is however contrary to the result obtained in a study by Garba who observed an increase in the plasma magnesium level of malaria patients suffering from P. falciparum parasite [34]. This disparity might be due to the different parasite counts and stages presented by the patients used for the study.…”
Section: Levels Of Electrolytes (Ca Mg K Na) In P Falciparum Infecontrasting
confidence: 99%
“…In another similar study, it was observed that the serum magnesium level in malaria patients increased about threefold compared to controls. In this study, they also mentioned that the increase in magnesium levels may be due to hemolysis since red blood cells contain high amounts of magnesium [31]. In another study, a relationship was found between magnesium levels on admission and 30-day mortality in pneumonia patients.…”
Section: Is the Increase In Magnesium Levels Cause Or Consequence?mentioning
confidence: 73%
“…Another similar result was observed in malaria patients that serum magnesium level was increased nearly 3 fold than controls. They mentioned increase of magnesium levels might be depended on hemolysis because red blood cells contain high amounts of magnesium [27]. In another study the association was found with magnesium levels on admission and 30-day mortality in patients with pneumonia.…”
Section: Resultsmentioning
confidence: 95%